ATTITUDE AND COMMUNITY PARTICIPATION IN THE PROVISION AND UTILIZATION OF GREEN OPEN SPACES OF THE YARD IN PALEMBANG - Putra, Bayu Rahmandra; Zulkifli, Hilda; Alfitri, Alfitri (BIOVALENTIA: Biological Research Journal, 2018)
The existence of private green open spacesofthe yard whichinvolves community participation in the provision and utilization of green open space has not been synergized with the city government program for the achievement of green open spaces mandated by the statutory regulations.With the statutory regulationson community involvement, this researchaimstoexamine the community attitudes andparticipation in the provision and utilization of green open space of the yard in Palembangby region with certain density.Dataanalysisused in thisresearch is a quantitative analysis based on questionnaires which collected from respondents whom have privatehome yard. Non-parametricstatisticaltests using the Mann-Whitney test to analyze the differences between the regions. Statistical tests of correlation Spearman rank and Somers'dusedto analyze the relationship between variables.The results showed the highscore of community attitude, while the participation of the community belong in the low score. Thereis a significant difference between community in low density regions with community in high density regions as shown in the correlation between the level of community attitudes toward community participation in the provision and utilization of green open space.